Queen Hynde - Hogg, James, 1770-1835 (Hogg, James, 1770-1835. Works. 1995, 1998)
The letters of Joseph Symson give us a glimpse into the life of an inland merchant who was also a member of England's urban elite. This text details his responses to the political, economic, and religious uncertainties of the early 18th century.